Lipopolysaccharide impacts murine CD103+ DC differentiation, altering the lung DC population balance. Issue 4 (12th February 2019) - Brassard, Julyanne; Maheux, Catherine; Langlois, Anick; Bernatchez, Emilie; Marsolais, David; Flamand, Nicolas; Blanchet, Marie‐Renee
Abstract: Conventional DCs are a heterogeneous population that bridge the innate and adaptive immune systems. The lung DC population comprises CD103 + XCR1 + DC1s and CD11b + DC2s; their various combined functions cover the whole spectrum of immune responses needed to maintain homeostasis. Here, we report that in vivo exposure to LPS leads to profound alterations in the proportions of CD103 + XCR1 + DCs in the lung. Using ex vivo LPS and TNF stimulations of murine lung and spleen‐isolated DCs, we show that this is partly due to a direct downregulation of the GM‐CSF‐induced DC CD103 expression. Furthermore, we demonstrate that LPS‐induced systemic inflammation alters the transcriptional signature of DC precursors toward a lower capacity to differentiate into XCR1 + DCs. Also, we report that TNF prevents the capacity of pre‐DCs to express CD103 upon maturation. Overall, our results indicate that exposure to LPS directly impacts the capacity of pre‐DCs to differentiate into XCR1 + DCs, in addition to lowering their capacity to express CD103. This leads to decreased proportions of CD103 + XCR1 + DCs in the lung, favoring CD11b + DCs, which likely plays a role in the break in homeostasis following LPS exposure, and in determining the nature of the immune response to LPS. Abstract : We demonstrate that exposure to LPS decreases CD103 + DCs proportions in the lung. This was explained by a systemic alteration in the capacity of DC precursors to differentiate into CD103 + DCs, in addition to a direct downregulating effect of LPS on de novo DC CD103 expression.